Progressive resistive loading on accessory expiratory muscles in tetraplegia - P. Gounden (AOSIS, 1990)
To investigate the effects of progressive resistive loading on accessory expiratory muscles in tetraplegia, 40 such patients undergoing standard pulmonary rehabilitation were randomly assigned to control (n = 20) and experimental (n = 20) groups. In total there were 8 women and 32 men with an average age of 31 years. Their lesions were between the fifth and eighth cervical segments. The majority of the patients sustained their injury during motor vehicle accidents. Prior to training, measurements of maximum expiratory mouth pressure and vital capacity were obtained from each group. The experimental group underwent eight weeks of training. The training involved the use of the PFLEX muscle trainer which allowed the patient to expire against a predetermined resistance. The initial resistive load was set at a level equivalent to 60 percent of the patient's maximum expiratory mouth pressure. Each subject was required to train for half an hour each day for six days a week. The resistive load was increased at two weekly intervals to ensure optimal loading throughout the training period the control group was excluded from any form of strenuous training but continued with the standard pulmonary care which involved conventional breathing exercises and assistance in coughing. The eight weeklong course of progressive resistive loading on accessory expiratory muscle showed a significant improvement in mean vital capacity from 1.48 L to 1.98 L (p = 0.0001) and a dramatic improvement in mean expiratory muscle strength from 43.76 cmH20 to 68 cmH2o) (p = 0.0001). Comparison of the values in the control group which were obtained eight weeks apart, showed no significant changes. The present finding that expiratory muscle strength in tetraplegics can be improved with specific training has important therapeutic implications. The increased PEmax should enable these subjects to generate higher intrathoracic pressure swings during coughing. Long term controlled studies should now be performed to determine the effects of this procedure on the clearance of bronchial secretions in such subjects.